2018
DOI: 10.15453/2168-6408.1400
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Adaptation as a Construct: A Scoping Review of Literature

Abstract: Background: This study integrates research on practice applications of the construct of occupational adaptation with occupational therapy and occupational science literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 24 publications
4
26
0
Order By: Relevance
“…Occupational adaptation is a construct used within occupational therapy to describe the process and/or outcome of the interaction between the person, occupation and environment in response to occupational challenge [24]. By performing daily activities, stroke survivors have been reported to gradually discover their strengths and weaknesses [25], which can lead to new priorities as well as negative feelings and the loss of occupations [1,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Occupational adaptation is a construct used within occupational therapy to describe the process and/or outcome of the interaction between the person, occupation and environment in response to occupational challenge [24]. By performing daily activities, stroke survivors have been reported to gradually discover their strengths and weaknesses [25], which can lead to new priorities as well as negative feelings and the loss of occupations [1,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Occupational adaptation is a concept used within occupational therapy to describe the process and/or outcome of the interaction between the person, occupation, and environment in response to occupational challenge [1]. Successful occupational adaptation results in a person responding masterfully and adaptively in the face of occupational challenge, to enable competence in the occupations associated with an individual's life roles [2].…”
Section: Introductionmentioning
confidence: 99%
“…Successful occupational adaptation results in a person responding masterfully and adaptively in the face of occupational challenge, to enable competence in the occupations associated with an individual's life roles [2]. However, like many concepts used within the profession, its conceptualisation lacks consensus across the profession and is open to considerable debate [1]. Incorporating earlier literature on adaptation by Llorens [3] and others [4][5][6][7], Schkade and Schultz [8] developed the first theoretical understanding of occupational adaptation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent scoping review by Grajo and Boisselle (2018), the construct of occupational adaptation and its application in occupational therapy practice was described. Although their review applied a different aim compared to the present review, some similarities in research gaps were found.…”
Section: Relative Masterymentioning
confidence: 99%